Prognostics and remaining useful life (RUL) estimation : predicting with confidence /: predicting with confidence. (2021) - Galar, Diego; Goebel, Kai; Sandborn, Peter A, 1959-; (Professor of mechanical engineering), Kumar, Uday
No abstract available